Risk attitudes and the structure of decision‐making: evidence from the Illinois hog industry. (4th October 2016) - Franken, Jason R.V.; Pennings, Joost M.E.; Garcia, Philip
Abstract: Research offers mixed evidence about the risk management decision‐making process of producers. Whether producers' characteristics drive behavior directly or through risk attitude remains a puzzle. We assess whether managerial/firm characteristics directly affect choices or if their influence occurs indirectly through impacts on risk attitude. The findings, which support indirect effects, indicate that failure to represent relationships between risk attitude, other characteristics, and behavior appropriately can mask the effect of risk attitude. A more complete understanding of the structure of decision‐making may assist economists, policymakers, and industry stakeholders in designing and targeting mechanisms to manage or transfer risk.